2010
DOI: 10.1111/j.1600-0897.2009.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

SHORT COMMUNICATION: CD3− CD56+ CD16+ Natural Killer Cells and Improvement of Pregnancy Outcome in IVF/ICSI Failure After Additional IVIG‐Treatment

Abstract: In a subgroup of RIF-patients with high level of CD56(+) CD16(+) NK-cells the additional application of IVIG leads to a favourable pregnancy outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 13 publications
3
40
0
1
Order By: Relevance
“…However, many clinical studies where IVIG were given to women suffering from recurrent spontaneous abortions, a noninflammatory condition, reported the opposite results, ie, decreased NK cell cytolytic activity and/or decreased number or percentage of circulating NK cells in treated women [35][36][37][38][39][41][42][43][44]. These discrepancies could be explained by the various conditions in which IVIG are used and, particularly, the existence or not of an inflammatory state.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, many clinical studies where IVIG were given to women suffering from recurrent spontaneous abortions, a noninflammatory condition, reported the opposite results, ie, decreased NK cell cytolytic activity and/or decreased number or percentage of circulating NK cells in treated women [35][36][37][38][39][41][42][43][44]. These discrepancies could be explained by the various conditions in which IVIG are used and, particularly, the existence or not of an inflammatory state.…”
Section: Discussionmentioning
confidence: 80%
“…Until recently, the possible role of NK cells in mediating the immunomodulatory effect of IVIG had never been mentioned. On the contrary, it was suggested that for preventing miscarriage, IVIG could act by inhibiting NK cells [35][36][37][38][39][40][41][42][43][44]. However, very recently, Chong et al [45] elegantly demonstrated that NK cells are necessary for the prevention of experimental autoimmune encephalomyelitis (EAE) by IVIG treatment.…”
Section: Discussionmentioning
confidence: 92%
“…Total 42% of IVIGpatient or 34.9% ⁄ embryo transfer had a live born baby, and the live born rate per embryo was 16.6%. 81 High levels of pNK cells were found to predict biochemical pregnancy and spontaneous abortions with normal karyotype in the next pregnancy. Elevated CD56 + cells in pregnant women predict loss of karyotypically normal conceptus: a specificity of 87% and positive predictive value of 78%.…”
Section: Pro-inflammatory Cytokines Induce Coagulationmentioning
confidence: 99%
“…Studies have shown that pregnant and non-pregnant RM patients may have elevated levels of NK cells [17,18] + and CD16 + ) declined in women who gave birth after IVIg treatment [23]. In the future, identifying immune biomarkers that characterize RM patients who may benefit from IVIg therapy is worth investigating.…”
mentioning
confidence: 99%